Transgenic mice expressing human tumour necrosis factor: a predictive genetic model of arthritis. - Keffer, J (1991)
We have generated transgenic mouse lines carrying and expressing wild-type and 3'-modified human tumour necrosis factor (hTNF-alpha, cachectin) transgenes. We show that correct, endotoxin-responsive and macrophage-specific hTNF gene expression can be established in transgenic mice and we present evidence that the 3'-region of the hTNF gene may be involved in macrophage-specific transcription. Transgenic mice carrying 3'-modified hTNF transgenes shows deregulated patterns of expression and interestingly develop chronic inflammatory polyarthritis. Treatment of these arthritic mice with a monoclonal antibody against human TNF completely prevents development of this disease. Our results indicate a direct involvement of TNF in the pathogenesis of arthritis. Transgenic mice which predictably develop arthritis represent a novel genetic model by which the pathogenesis and treatment of this disease in humans may be further investigated.